124k views
3 votes
Please help me ??!?!?

Please help me ??!?!?-example-1

2 Answers

2 votes
2x-6-(3x+9)

2x-6-3x-9

-x-15 = (f-g)(x)
User Jon Mitten
by
4.9k points
1 vote

For this case we have given two functions, f (x) and g (x).

So:


(f-g) (x) = f (x) -g (x)

We have:


f (x) = 2x-6\\g (x) = 3x + 9

So:


(f-g) (x) = 2x-6- (3x + 9)

Taking into account that
- * + = -


(f-g) (x) = 2x-6-3x-9

Different signs are subtracted and the sign of the major is placed.


(f-g) (x) = - x-15

Answer:


(f-g) (x) = - x-15

Option D

User Dakab
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.